Serpin–4 Facilitates Baculovirus Infection by Inhibiting Melanization in Asian Corn Borer, Ostrinia furnacalis (Guenée) - Ji, Jiayue; Shen, Dongxu; Zhang, Shasha; Wang, Lei; An, Chunju (Frontiers in Immunology, 2022)
Phenoloxidase (PO)–catalyzed melanization is a vital immune response in insects for defense against pathogen infection. This process is mediated by clip domain serine proteases and regulated by members of the serpin superfamily. We here revealed that the infection of Autographa californica multicapsid nucleopolyhedrovirus (AcMNPV) significantly inhibited the PO activity in Ostrinia furnacalis hemolymph and induced the expression of O. furnacalis serpin–4. Addition of recombinant serpin-4 protein to O. furnacalis hemolymph resulted in a great increase of AcMNPV copies. Serpin-4 significantly suppressed the PO activity and the amidase activity in cleaving colorimetric substrate IEARpNA (IEARase activity) of hemolymph. Further experiments indicated it formed covalent complexes with three serine proteases (SP1, SP13 and SP105) and prevented them from cleaving their cognate downstream proteases in vitro. Altogether, O. furnacalis melanization restricted AcMNPV replication and serpin-4 facilitated AcMNPV infection by inhibiting serine proteases, SP1, SP13, and SP105 which were all involved in the melanization response.